Parâmetros nutricionais de novilhas Nelore em pastejo de capim marandu recebendo suplemento energético, proteico e múltiplo no período de transição seca-águas - Pesqueira-Silva, Lilian Chambó Rondena; Zervoudakis, Joanis Tilemahos; De Araújo, Claúdio Vieira; Cabral, Luciano Da Silva; Hatamoto-Zervoudakis, Luciana Keiko; De Oliveira, André Alves [UNESP]; Da Silva-Marques, Renata Pereira (Universidade Estadual de Londrina, 2015)
The objective was to evaluate thein take and digestibility of nutrients, ammonia nitrogen (NH3-N) in the rumen and serum urea nitrogen (BUN) in Nellore heifers in grass Marandu recreated during the transition period dry energy supplement receiving waters, protein and multiple. We used four heifers with average body weight and initial age of 189.5 kg and 12 months respectively, distributed in four paddocks of 0.25 ha each. The design was a 4x4 Latin square (four supplements and four periods of 14 days). The supplements were: energy supplement (ES) protein (PS) and multiple (MS), provided the amount of 1 kg animal day-1 in addition to supplement containing commercial mineral mixture ad libitum (MM). The concentrate supplementation did not increase intakes of dry matter, total organic matter and forage. The additional SP provided greater (P<0,0001) intake of crude protein (CP). The SE and SP supplement resulted ingreater ether extract intake. The CP was higher (P<0.0001) in animals supplemented with SP and SM. Immediately before and four hours after supplementation higher concentrations of ruminal NH3-N were observed for the SM and SP supplements. There were no differences for ser um urea nitrogen (BUN). The use of protein supplement and multiple provided the best fit of the rumen of heifers during the transition period dry-rainy fed on grasses Marandu environment.
Nutritional parameters of Nellore heifers grazing in grass marandu receiving energy, protein and multiple supplement the dry-rainy transition period
Keywords: Digestibility; Intake; Ruminal ammonia; Suplementation